The influence of the gini ratio and inflation on the Human Development Index (HDI) - Reka Ramadhan; Intan Deanida Pertiwi (Privietlab, 2025)
The purpose of this study is to examine how inflation and the Gini Ratio affect Indonesia's Human Development Index (HDI).Multiple linear regression using secondary data was used for the analysis.The results show that the HDI is negatively and significantly impacted by inflation, suggesting that rising inflation can lower the quality of human development by stifling people's purchasing power and restricting access to healthcare and education.Income inequality has not yet emerged as a major factor impacting HDI accomplishment during the study period, as seen by the Gini Ratio's lack of a substantial impact on the HDI.The HDI is significantly impacted by both independent variables at the same time, with the model accounting for 23.9% of the variation in the HDI and other factors influencing the remaining variation.These results emphasize how crucial inflation control measures are to promoting the enhancement of Indonesia's human development, especially with regard to food items and essentials.